Medical Skills in a Clinical Presentation-Based Curriculum: Approach to the Patient With Nausea and Vomiting - Gordon Woods (Association of American Medical Colleges, 2015)
Abstract Introduction The materials in this submission guide clinical faculty as they organize and present a learning session for preclerkship medical students on the approach to the adult patient with nausea and vomiting. These materials were originally developed for the Medical Skills Course at the Texas Tech University Health Sciences Center at the Paul L. Foster School of Medicine (PLFSOM) in El Paso, Texas. Methods During the session, students individually (or in pairs) interview and examine a female standardized patient portraying a 41-year-old woman with recurrent episodes of nausea and vomiting. After the encounter, students write a subjective, objective, assessment, plan (SOAP) note using the USMLE format, receive feedback from the standardized patient, receive feedback from their peer observer (if present), and debrief in a group discussion with a faculty member. The submitted materials include a readiness assurance quiz, preparatory exam room guide and video, summary outline that students can use during the standardized patient encounter, check sheet to guide peer observer feedback, and standardized patient case blueprint. There are also documents that describe the presentation-based curriculum and the organization of the standardized patient program at PLFSOM. Results By several measures, the PLFSOM clinical presentation curriculum can be considered as successful. Every year so far, the students at PLFSOM have scored above the national average on USMLE step 1 and step 2 exams. Graduates of the curriculum have been very successful in matching at high-level residency programs. Based on student evaluations, the Medical Skills Course at PLFSOM is the highest rated course in the curriculum, achieving a score of 4.7 on a scale of 1-5 for overall effectiveness. Informal comments gathered from third-year students indicate that they are able to quickly engage in clinical activities at the beginning of the third year. Discussion These materials would be of interest to preclerkship clinical skills instructors who would like to present a learning session to students on gastrointestinal diagnosis, particularly motility disorders.